If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
((6*x+10)^3)/7 = 0
6*x+10 = 0 // - 10
6*x = -10 // : 6
x = -10/6
x = -5/3
x in { -5/3, -5/3, -5/3 }
| x=35-782 | | 5(2y+4)+2(5-y)=6 | | 5X-17=-2X-4 | | 7-3(10-2y)=-5 | | 5X-17=2X-4 | | 3(2x-4)-(5x+2)=11 | | 3(4x+4)-2(3-x)=48 | | 13x+30=6x+114 | | 4x-2(3x+10)=8 | | 10-2x-5=-4x+10-3x | | 5-3x+5=5+2x | | 29-60/7 | | 6x+7=133-8x | | 6-5x-2x=3-5x | | X^2-9x-81= | | 3+2x-4x=4-x+4 | | 3(x-6)=72/12 | | 5x+0.8=x | | 7/x=5/4x+1 | | r^2-30r+29= | | 17-3a=5a+1 | | 3u-25u/6+20=18 | | 360=2x(x+3) | | 4(5+3)=3c-5 | | -2/7x=10 | | 3x^2+(k-2)x+k=0 | | 3a-2b-(2a-3b)= | | 49v^2-121f^2= | | 4E+07= | | y=x^2-4x-8 | | 18x-7=43 | | 4a^2+28ap+49p^2= |